Understanding medication-related burden from patient perspectives: a qualitative study testing the applicability of the conceptual model among chronically ill outpatients in Finland - Marja Airaksinen; Katri Hämeen-Anttila; Heidi Mikkola; Maarit Dimitrow; Emilia Laukkanen (BMJ Open)
Objectives Disease self-management and medication therapy can cause burden to patients that can influence adherence. The conceptual model ‘patients’ lived experience with medicine’ (PLEM) brings new insights into medication-related burden (MRB) from patient perspective. This study aimed to test the applicability of the PLEM model by interviewing chronically ill patients in Finland and to investigate the MRB experienced by the Finnish patients.Design Focus group discussion study conducted online via Zoom. Directed qualitative content analysis guided by the PLEM model.Setting Outpatient primary care in Finland.Participants Chronically ill outpatients (n=14) divided into five focus groups according to their chronic condition: asthma (n=3), heart disease (n=3), diabetes (n=6), intestinal disease (n=2).Results Our findings were mainly in line with the PLEM model although some new contributing factors to MRB emerged. In general, the participants were satisfied with their medication, and that it enabled them to live normal lives. The most common causes of MRB were medication routines and the healthcare system. The participants introduced two new aspects contributing to MRB: medication-related environmental anxiety associated with the waste resulting from medicine use, and the effect of medication use on their working life. Our findings are consistent with previous findings that a higher level of MRB may lead to independently modifying the medication regimen or not taking the medicine.Conclusions Our findings provide further evidence that the PLEM model is an applicable tool also in the Finnish context for gaining better understanding of MRB in chronically ill patients self-managing their long-term medications. The model provides a promising tool to understand the connection between MRB and the rationale for not always taking medicines as prescribed. Further research is needed to explore the potential of the model in extending patient perspectives in chronic disease management.